Association of Lactate Dehydrogenase and Predictive Biomarkers in Primary Lung and Breast Tumors with Metastatic Bone Disease - Muhammad Alfa Septiano Yunus; Rhyan Dharma Saputra; Mujaddid Idulhaq (Indonesian Journal of Global Health Research, 2026)
Metastatic Bone Disease (MBD) is one of the most aggressive forms of tumor spread, reshaping the tumor microenvironment into a hypoxic and acidic state that enhances lactate dehydrogenase (LDH) activity. Primary lung and breast tumors possess distinct predictive biomarkers, EGFR and HER2, which drive the Warburg effect and further elevate LDH levels. MBD often leads to skeletal-related events that impair quality of life and require prompt, comprehensive management. This study aimed to examine the the association between LDH levels and EGFR/HER2 expression, and evaluate LDH’s potential as an early, efficient indicator for clinical decision-making in MBD patients. Method: A cross-sectional study was conducted through medical record reviews at Dr. Moewardi General Hospital, Surakarta. Samples included patients with primary lung and breast tumors diagnosed with MBD from 2023–2024, selected using total sampling. Serum LDH, EGFR, and HER2 data were then retrieved from the electronic medical record. Associations between LDH and EGFR/HER2 were analyzed using binary logistic regression. LDH showed a positive but statistically non-significant association with EGFR mutation status in lung cancer patients with MBD (OR=0.999, 95% CI=0.994–1.004, p=0.713) and with HER2 status in breast cancer patients with MBD (OR=1.750, 95% CI=0.084–36.287, p=0.718). LDH was positively associated with EGFR and HER2 expression in MBD patients, though the associations were not statistically significant.